PERAN PENTING AUDIT MUTU INTERNAL - Yanti, Yovi; Radiana, Usman (UHN IGB Sugriwa Denpasar, 2024)
This research aims to fully describe internal quality audits, namely the important role of internal quality audits and internal audits in education in Indonesia. In obtaining data for this research, a qualitative approach of the Systematic Literature Review type was used, by collecting data from books, journals and articles. Data analysis was carried out using the PRISMA method, there were 5 stages used, namely determining eligibility criteria, determining sources of information, selecting literature, collecting data, and selecting data items. With this method it can be obtained from various sources including journals, books, documentation, the internet and libraries. The research results found that: 1) The important role of internal quality audit is that there are four main practical elements, namely verification of written records, policy analysis, evaluation of the logic and completeness of procedures, internal services, and staff to ensure that procedures are efficient and in accordance with organizational policies and reporting recommendations. improvements to superior management. 2). Internal Audit of Education in Indonesia, Joint audits can play an important role in the implementation of education, so that they can find out various problems that occur in operational activities in schools, the causes of these problems, and then think about solutions to these problems. From the implementation of this audit, it is hoped that it can improve the quality of educational services supported by transparency and accountability in the management of educational services Keywords: The important role of internal quality audi, education in Indonesia